2020
DOI: 10.1177/0093854820949603
|View full text |Cite
|
Sign up to set email alerts
|

Narratives of Gang Disengagement Among Former Gang Members in South Africa

Abstract: Understanding gang disengagement is important for the development of effective interventions. This research sought to examine how former South African gang members understand their gang disengagement. Two rounds of life history interviews were conducted with 12 former gang members. Thematic narrative analysis was used to analyze the interview data. Findings revealed that personal agency was key to the participants’ disengagement, which included forming a purposive intention to change, committing to and maintai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 34 publications
1
1
0
Order By: Relevance
“…Two of the participants specifically recalled how the birth of a child, whose upbringing they really wanted to be part of, also played a major role in their non-involvement in gangs. This is consistent with the findings of a study by Moloney, MacKenzie, Hunt and Joe-Laidle (2009:7), where participants referred to fatherhood as a 'turning point' in their lives and key to their rejection of a life of gangsterism and crime: Kelly and Ward (2017) found that fatherhood resulted in young males leaving the life of gangsterism for the sake of their children. Fatherhood supported them in leaving the gang life because it gave them a new-found sense of meaning and purpose; this is consistent with the study, stated above, by Moloney et al (2009).…”
Section: Sub-theme 44 Fatherhoodsupporting
confidence: 90%
“…Two of the participants specifically recalled how the birth of a child, whose upbringing they really wanted to be part of, also played a major role in their non-involvement in gangs. This is consistent with the findings of a study by Moloney, MacKenzie, Hunt and Joe-Laidle (2009:7), where participants referred to fatherhood as a 'turning point' in their lives and key to their rejection of a life of gangsterism and crime: Kelly and Ward (2017) found that fatherhood resulted in young males leaving the life of gangsterism for the sake of their children. Fatherhood supported them in leaving the gang life because it gave them a new-found sense of meaning and purpose; this is consistent with the study, stated above, by Moloney et al (2009).…”
Section: Sub-theme 44 Fatherhoodsupporting
confidence: 90%
“…A question arises as to whether women’s criminal behavior can be explained solely by viewing them as victims of circumstances? This is in light of the fact that many approaches and studies referred to male criminal behavior as a rational choice and highlights the need to take responsibility to begin rehabilitating processes (Charlopova et al, 2020; Kelly & Ward, 2020).…”
mentioning
confidence: 99%